Development of Local History Digital Modules to Increase the Learning Motivation of Senior High School Students - Sianturi, Charlis (Jurnal Pendidikan Progresif, 2025)
Abstract: Development of Local History Digital Modules to Increase the Learning Motivation of Senior High School Students. Objectives: This study aims to develop a local history-based digital module on Willem Iskandar's struggle for education in North Sumatra and measure its effectiveness in increasing students' learning motivation. Methods: This research uses the Research and Development (R&D) method with the ADDIE model, which includes five stages: analysis, design, development, implementation, and evaluation. The sampling technique used was a saturated sample because the entire population in this study was taken as a sample, consisting of 55 grade XI students and one history teacher at SMAN 2 Doloksanggul. Research instruments in the form of interviews, observations, and questionnaires were used to measure the validity, practicality, and effectiveness of the module. Findings: The validation results from material experts showed a percentage of feasibility of 82.35% and from media experts of 83.33%, both in the very feasible category. The practicality test conducted by teachers and students resulted in scores of 88.24% and 80.63%, respectively, which also showed the module was very feasible to use in the learning process. The results showed that the digital local history module can increase students' learning motivation. A paired t-test showed a significant increase in students' learning motivation after using the digital module, with a significance value of 0.001. In addition, the N-Gain test showed the effectiveness of the module with a value of 0.54, which is quite effective to increase students' history learning motivation. Conclusion: The results showed that the developed local history digital module had a significant effect on increasing the learning motivation of grade XI students. The implication of this study is the importance of developing a more comprehensive training program for teachers in mastering digital technology, as well as expanding the focus of research by exploring other factors besides digitalization in increasing student learning motivation. Keywords: digital module, local history, learning motivation.